The uses of shopping: Richard Hoggart goes to Woolworth's. Issue 12 (2nd December 2021) - Bowlby, Rachel
ABSTRACT: In The Uses of Literacy and in the many autobiographical works of his later years, Richard Hoggart wrote about shops and shopping. Taking a distance from the adverse stance of the mid-century literary world to 'consumer society' in all its forms, Hoggart consistently represented himself as someone who liked to shop. This essay looks at the changing shopping experiences that Hoggart described, and at the rare distinctiveness of this lifelong interest, for a man of his time and cultural places. It concentrates mainly on the shops he wrote about close to the various homes of his life, but it also briefly considers Hoggart's accounts of contrasting experiences of touristic consumption: the conviviality of the working-class coach trip, as opposed to the isolations of remote retirement travel.